APPLICATION OF A STUDENT-CENTERED APPROACH IN DEVELOPING COMMUNICATIVE GRAMMAR COMPETENCE DURING ENGLISH LESSONS - Kismetova G.N.; Oryngali N.S. (Interdisciplinary Science Studies, 2025)
The article investigates the application of a student-centered approach to enhance communicative grammar competence among English as a Foreign Language (EFL) learners. This approach, rooted in constructivist theories, focuses on personalization, contextualization, and learner autonomy. The paper incorporates theoretical underpinnings, practical strategies, and a case study from secondary school teaching experience in Kazakhstan, illustrating its impact on 8th and 9th-grade students' grammar proficiency. The discussion also highlights the contributions of Kazakhstani researchers to language pedagogy, particularly in trilingual education, showcasing the importance of innovative teaching methodologies in multilingual contexts. The findings underline the benefits of a student-centered approach in fostering meaningful language use, learner engagement, and autonomy